Development of regression model to investigate the correlation of selected input parameters to the thread consumption of over-lock stitch 514 - Niroshan, T.S. (University of Jaffna, 2021)
The cost of manufacturing and distribution of apparel products are highly depended on the sewing thread consumption. Thus, the calculation of sewing thread consumption has to be done accurately using effective methods.Due to the inefficiency of the existing formulae, the predictions of thread requirement became inaccurate. The consumption calculations exhibit significant error percentages due to the ignorance of important parameters which effect on thread consumption. This study investigates on correlation of many parameters such as GSM, seam width,SPI, frequency, thickness of fabric and yarn count to thread consumption of over-lock stitch 514. The existing thread consumption formulae are optimized by considering new parameters, using regression analysis and geometrical modelling techniques. For the over-lock stitch 514, results indicate that above parameters significantly affect in determination of the thread consumption. This particular method addresses the following issues: In accurate consumption calculation, Excess seam length or inaccurate seam length, Use of predefined thread consumption factors and use to calculate thread consumption by only considering machine type. The error analysis of proposed formulae was performed to indicate that the proposed formulae more accurate compared to the current method of predicting sewing thread consumption. Therefore, the proposed formulae are expected to be a better approach tocalculate thread consumption of over lock stitch 514.
Keywords: GSM; Over-lock stitch; Thread consumption; Seam length; Regression model